Analisis Rancangan Rangka Kompor Hemat Energi Berbahan Bakar Air - muhammad rifqi aditya; Armila Armila; Rudi Kurniawan Arief (Jurnal Teknik Mesin, 2022)
Analysis of the design of this energy-efficient stove for distributing the results from the HHO (Hydrogen Hydrogen Oxygen) generator and turning this HHO into a fire. The purpose of this analysis is to determine the strength of the stove frame with the maximum load it can accommodate. This stove is made with a design and structure that is larger in scale with new innovations that combine metal materials and concrete materials where the two materials are combined to create a sturdy and strong stove structure, the structure of this stove is innovated from the stove in general. The result of the force diagram shows that the bending stress of the weld seam is smaller than the allowable stress of the material, namely: wb = 8, 03×10-3 180 N/mm2. Therefore the stove is safe to use.